2013
DOI: 10.3109/13816810.2013.768673
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Phenotype in Ten Unrelated Japanese Patients with Mutations in theEYSGene

Abstract: Although additional studies with more patients with mutations of the EYS gene are required, it appears that patients share a relatively uniform phenotype with near-normal central visual function up to their twenties. The patients homozygous for the c.4957_4958insA mutation showed a uniform course of visual acuity changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Altogether, these findings indicate that this Alu insertion is not only clearly pathogenic, but it is also a rather prevalent cause of retinal degeneration within the Japanese islands at the level of a single allele (1.8% of all HRD Japanese patients), possibly second only to the most frequent mutation so far identified in this country, i.e. NM_001142800.1:c.4957dup in EYS [24][25][26] .…”
Section: An Alu Insertion In Rp1 Is a Prevalent Cause Of Hrd In Japanmentioning
confidence: 75%
“…Altogether, these findings indicate that this Alu insertion is not only clearly pathogenic, but it is also a rather prevalent cause of retinal degeneration within the Japanese islands at the level of a single allele (1.8% of all HRD Japanese patients), possibly second only to the most frequent mutation so far identified in this country, i.e. NM_001142800.1:c.4957dup in EYS [24][25][26] .…”
Section: An Alu Insertion In Rp1 Is a Prevalent Cause Of Hrd In Japanmentioning
confidence: 75%
“…Each separate variant homozygous, as well as the identical compound heterozygous combination of these variants, were previously identified as causal in RP patients. 9,[30][31][32] The third case was a French patient with compound heterozygous variants, p.(Trp558*) and p.(Asn745-Ser). The pathogenicity of the missense variant was questionable, as it proved to be not conserved, and the pathogenicity is uncertain according to the ACMG classification.…”
Section: Discussionmentioning
confidence: 99%
“…However, age, logMAR visual acuity, and MD value were not statistically significant prognostic factors in the present study, although a previous study has reported that the extent of visual fields constriction seemed to correlate better with age than with visual acuity. 10 These findings help to explain the disease course to patients in clinical practice; that is, disease progression of RP patients with EYS mutations with relatively longer ISe should be slow, whereas that of the patients with relatively shorter ISe should be rapid. However, we cannot predict the degree of disease progression from age, visual acuity, and visual field.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Furthermore, a report has described that EYS-associated RP patients share a relatively uniform phenotype with near-normal central visual function up to their 20s. 10 We have previously reported that severity of RP patients with EYS mutations was relatively moderate among RP patients with various mutations. 11 Thus, we encounter RP patients with EYS mutations at relatively high frequency in daily clinical consultation except detection for causative gene mutations, and RP patients with EYS mutations have a representative feature in RP.…”
Section: Introductionmentioning
confidence: 99%